2007
DOI: 10.1021/jp073687j
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Binding of Fluorine to Aluminum in High Peralkaline Aluminosilicate Glasses

Abstract: For two series of fluoride-containing aluminosilicate glasses of high peralkaline type, we apply 27Al, 19F, 29Si, and 23Na NMR spectroscopy to understand the structural changes introduced by the addition of alkali fluorides. Adding fluoride in concentrations above the solubility limit causes crystallization of different phases in sodium and potassium glasses despite identical composition. However, the NMR spectra reveal that the structural evolution of the precrystallized states is similar in both series. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
2
20
2
2
Order By: Relevance
“…As the Al:Si ratio is increased, the Al is incorporated in the network as a Q 4 (4Si) species, which increases the crosslinking of the glass structure. In contrast to previous reports of similar fluoro-aluminosilicate glasses 36,37 , for the However, in contrast to these studies, in our glasses, though the ratio of Al:F (Table 3) is close to the previous compositions, we have much higher fraction of Group II Na NMR data indicates that the distribution of sodium sites is invariant within the series.…”
contrasting
confidence: 99%
“…As the Al:Si ratio is increased, the Al is incorporated in the network as a Q 4 (4Si) species, which increases the crosslinking of the glass structure. In contrast to previous reports of similar fluoro-aluminosilicate glasses 36,37 , for the However, in contrast to these studies, in our glasses, though the ratio of Al:F (Table 3) is close to the previous compositions, we have much higher fraction of Group II Na NMR data indicates that the distribution of sodium sites is invariant within the series.…”
contrasting
confidence: 99%
“…(3) indicates that the activation energy for aluminosilicate glass (FGA_0) is slightly higher than Si-O bond dissociation energy (360-430 kJ mol -1 ) in silicate glasses [18]. [20]. That is why it can be assumed that obtained in the study values apply to aluminosilica oxide network crystallization.…”
Section: Methodsmentioning
confidence: 91%
“…Remaining 15% is the contribution from À52, À9, and 116 ppm peaks. Based on the previous 19 F MAS NMR studies on different types of borosilicate glasses containing F À ions [7][8][9][10][11]13], the peaks around 50, 30, and À9 ppm have been attributed to FNa(x)Ba(y) type linkages having unknown values of x and y. Structural units having highest value of x appears around À9 ppm and that having highest value of y appears around 50 ppm.…”
Section: Methodsmentioning
confidence: 95%
“…In a related study [6] we have also reported that simultaneous incorporation of both thorium and uranium oxides in barium-sodium borosilicate glass results in the phase separation of ThO 2 when uranium oxide incorporation exceeds 5 wt% along with 15.87 wt% of ThO 2 in the glass. There are numerous investigations on the structural aspects of fluoride ion containing silicate/alumino-silicate glasses investigated by 19 F NMR and XPS techniques [7][8][9][10][11]. Based on these studies it has been concluded that most of the F À ions in the glass exist as F-M(n) (fluorine with unknown number of network modifying cations like Na + , Ca 2+ , Ba 2+ etc.)…”
Section: Introductionmentioning
confidence: 99%